EVOLUTION OF THE GAME OF FOOTBALL IN TERMS OF RULES AND FORMATIONS OF PLAY (University Arena, 2025)
The game of football has, throughout its history, provided moments of unparalleled spectacle and popularity, with a global following. From the earliest documented instances of ball games played with the feet, without clearly defined rules, to the most sophisticated styles of play observed in modern times, the evolution of football has been a continuous process. The development of football has been influenced by the contributions of renowned coaches and players who have introduced innovative techniques, such as "tiki-taka" and the "Galacticos." These innovations have shaped the evolution of the sport in response to the demands of the modern era. A number of renowned coaches, including Helenio Herrera, Sir Alex Ferguson, Rinus Michels, Enzo Bearzot, Johan Cruyff, Pep Guardiola and others, have employed creativity to devise innovative systems of play and principles to enhance the abilities of their players, with the objective of achieving victories. The objective of this study was to analyse the literature onthe subject and illustrate the game systems that were employed in the earliest official matches and how they evolved in response to changes in the regulations. Over time, international governing bodies have issued regulations that have compelled coaches to be creative and identify optimal strategies for their teams to achieve victory and perform at their best. Each system of play has been described in chronological order, with the aim of establishing a correlation between the rules of play and the systems employed at the time. The field of football is undergoing continuous development, with technology playing an increasingly significant role inthe conduct of matches. Software and statistical data are being used by referees and coaches to inform decision-making, thereby reducing the time required for decision-making.
Keywords: history of football; formations of play; rules